Assessment Knowledge and Attitudes of Baghdad University Students’ toward Human immunodeficiency virus / acquired immunodeficiency syndrome - mehdi, Sarab; Al-Saffar, fatin (Iraqi National Journal of Nursing Specialties, 2013)
Objective(s): To assess Baghdad University students’ knowledge and attitudes toward HIV/AIDS, and to find outthe relationship of Baghdad University students’ knowledge and attitudes with certain variables (gender,socioeconomic status, field of study).Methodology: A descriptive analytic study was used to assess the knowledge and attitudes of Baghdad UniversityStudents’ toward HIV/AIDS. The study was conducted (November 1st 2012 to July 15th 2013). A non-probability(purposive sample) of 400 students (males-138 and females-262) were selected from four colleges and they werein the fourth class, a probability (stratified random) method was used to select four colleges at University ofBaghdad as a study setting. The data was collected for the present study through the self-filling technique by usingthe questionnaire that designed by the researchers. Validity through a panel of (16) experts and the reliability ofthe questionnaire is determined through the pilot study.Results: The findings of present study revealed that the majority of the study samples were female (65.5%),(45.0%) of them were at age 22 yrs. the majority of them (85.8%) were unmarried (single), (50.2%) of them werefrom scientific field, (32%) of them were selected from English language department, the vast majority (92.8%) ofthem were urban residency, the majority of them (41.5%) were from moderate & (41.0%) were from high socioeconomic class. The assessment of knowledge is not affected by demographic characteristic except (field of study,and department, as well as occupation of student’s father). Also the results showed that students’ knowledgeabout AIDS was good/ or adequate, as for their attitudes toward patients with AIDS were negative.Recommendations: The study recommended to increased students’ awareness through the mass media about therisks of this disease and how to prevent it. Increase lectures and discussions about HIV/AIDS that increasestudents’ information.